Identification of the Tumor Immune Microenvironment and Therapeutic Biomarkers by a Novel Molecular Subtype Based on Aging-Related Genes in Hepatocellular Carcinoma - Cai, Dong; Zhao, Zhibo; Hu, Jiejun; Dai, Xin; Zhong, Guochao; Gong, Jianping; Qi, Feng (Frontiers in Surgery, 2022)
Background: Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors with poor prognosis. Increasing evidence has revealed that immune cells and checkpoints in the tumor microenvironment(TME), and aging are associated with prognosis of HCC. While the association between aging and the tumor immune microenvironment in HCC is still unclear. Methods: RNA expression profiles and clinical data of HCC were downloaded from TCGA and GEO databases. Based on differentially expressed aging-related genes, unsupervised clustering was used to identify a novel molecular subtype in HCC. The features of immune cells infiltration and checkpoints were furtherly explored through CIBERSORTx. Enrichment analysis, univariate and multivariate Cox analysis were conducted to construct a 3-gene model for predicting prognosis and chemosensitivity. Finally, mRNA and protein expression levels of the 3 genes were verified in HCC and other cancer through databases and experiments. Results: 11 differentially expressed AGs(GHR, APOC3, FOXM1, PON1, TOP2A, FEN1, HELLS, BUB1B, PPARGC1A, PRKDC and H2AFX) correlated with the prognosis of HCC were used to divide HCC into two subtypes in which the prognosis is different. In the cluster 2 with poorer prognosis, the infiltration of naïve B cells and monocytes was lower while the infiltration of M0 macrophages was higher in the TCGA and GEO cohorts. In addition, the TCGA cohort indicated that the microenvironment of cluster 2 had more immunosuppressive through immune checkpoints. Enrichment analysis suggested that the MYC and E2F targets were positively associated with cluster 2 in the TCGA and GEO cohorts. Additionally, 3 genes(HMGCS2, SLC22A1 and G6PD) were screened to construct the prognostic model through univariate/multivariate Cox analysis. Then, the model was validated in the TCGA validation set and GEO data set(GSE54236). Then, Cox analysis indicated that the risk score was an independent prognostic factor and patients in the high-risk group were sensitive to multiple targeted drugs(sorafenib, gemcitabine, rapamycin, etc.). Finally, significantly differential expression of the 3 genes was identified in pan-cancers. Conclusion: We systematically described the immune differences in TME between the molecular subtypes based on aging-related genes and constructed a novel three-gene signature to predict the prognosis and chemosensitivity in patients with HCC.